2019
DOI: 10.1002/jcb.29585
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl alcohol modified polyvinylidene fluoride‐graphene oxide scaffold promotes osteogenic differentiation potential of human induced pluripotent stem cells

Abstract: Tissue engineering is fast becoming a key approach in bone medicine studies. Designing the ideally desirable combination of stem cells and scaffolds are at the hurt of efforts for producing implantable bone substitutes. Clinical application of stem cells could be associated with serious limitations, and engineering scaffolds that are able to imitate the important features of extracellular matrix is a major area of challenges within the field. In this study, electrospun scaffolds of polyvinylidene fluoride (PVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Cao et al demonstrated that ATDC5 cell line proliferation was increased significantly when grown on nanofibrous scaffold made by Chitosan/Poly(vinyl alcohol) (PVA)/GO compared to the Chitosan/PVA during two weeks culture period 34 . In another two studies published by our group, we demonstrated that viability, proliferation rate and osteogenic differentiation capacity of human induced pluripotent stem cells was increased significantly while grown on the Polyvinylidene fluoride (PVDF)/PVA/GO and PVDF/GO nanofibrous scaffold compared to the those cells cultured on both scaffolds without GO 35,36 . The results of the mechanical behavior of scaffolds showed that with increasing GO, the mechanical strength has increased while their tendency to break decreased.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Cao et al demonstrated that ATDC5 cell line proliferation was increased significantly when grown on nanofibrous scaffold made by Chitosan/Poly(vinyl alcohol) (PVA)/GO compared to the Chitosan/PVA during two weeks culture period 34 . In another two studies published by our group, we demonstrated that viability, proliferation rate and osteogenic differentiation capacity of human induced pluripotent stem cells was increased significantly while grown on the Polyvinylidene fluoride (PVDF)/PVA/GO and PVDF/GO nanofibrous scaffold compared to the those cells cultured on both scaffolds without GO 35,36 . The results of the mechanical behavior of scaffolds showed that with increasing GO, the mechanical strength has increased while their tendency to break decreased.…”
Section: Discussionmentioning
confidence: 74%
“…34 In another two studies published by our group, we demonstrated that viability, proliferation rate and osteogenic differentiation capacity of human induced pluripotent stem cells was increased significantly while grown on the Polyvinylidene fluoride (PVDF)/PVA/GO and PVDF/GO nanofibrous scaffold compared to the those cells cultured on both scaffolds without GO. 35,36 The results of the mechanical behavior of scaffolds showed that with increasing GO, the mechanical strength has increased while their tendency to break decreased. This is due to the increase in the surface-to-volume ratio in the composite, which makes the transfer of force to GO more efficient.…”
Section: Osteoinductivity Characterization 331 | Alp Activity Andmentioning
confidence: 99%
“…The other method was to use the excellent electrical conductivity of GDs to improve the performances of piezoelectric biomaterials that could bring desired electrical stimulation for new bone formation under biomechanical environment in vivo. 96,97 In addition to the excellent electrical conductivity of GDs themselves, GDs could also enhance the electrical output performance of the piezoelectric biomaterials by changing the phase structure of the matrix. For example, Shuai et al 96 introduced GO into polyvinylidene fluoride (PVDF) to fabricate composite scaffolds for bone repair.…”
Section: Excellent Electrical Propertiesmentioning
confidence: 99%
“…It can be claimed that the increase of the surface of the electrical polarity of PVA NFs upon embedding PE-CS-AuNPs could enhance the adhesion and proliferation of fibroblasts. 59 In addition, PE was reported as a cosmeceutical component due to its ability to enhance dermal fibroblasts. 15 The anti-inflammatory and antioxidant properties of PE could protect the HFF-1 from oxidative stress and maintain their normal growth.…”
Section: Resultsmentioning
confidence: 99%